SELECTION OF PROMISING LINES FROM F4 GENERATION OF CHICK PEA GENOTYPES THROUGH CORRELATION AND PATH COEFFICIENT ANALYSIS - P. S. JADHAV; A. H. RATHOD; R. R. LIPANE; P. B. BERAD (The Bioscan, 2014)
The investigation was conducted with 45 genotypes of Chickpea out of 30 elite lines of F4 generation, 12 parental lines and 3 checks in randomized block design which were evaluated for correlation among agronomical yield components and their direct and indirect effects on seed yield. The correlation coefficient analysis revealed seed yield per plant exhibited positive and significant correlation with plant height (0.2736, 0.2957), number of branches per plant (0.4912, 0.5492), pods per plant (0.4726, 0.4837), number of seeds per plant (0.4736, 0.4899), 100 seed weight (0.5892, 0.6193) and harvest index (0.4453, 0.4806) at both genotypic and phenotypic level. The characters biological yield per plant and days to maturity depicted positive but no significant association and days to 50% flowering exhibited negative and non significant association with seed yield per plant at both genotypic and phenotypic level. The perusal of path analysis indicated that the high positive direct effect exhibited by branches per plant (0.2782) followed by 100-seed weight (0.2415), harvest index (0.2107) and number of pods per plant (0.1569) on grain yield at both genotypic and phenotypic level. Thus the study suggest that plant height, number of branches per plant, pods per plant, number of seeds per plant, 100 seed weight and harvest index are important traits for the selection criteria in crop improvement program of chickpea.